Folate-modified silicon carbide nanoparticles as multiphoton imaging nanoprobes for cancer-cell-specific labeling. Issue 44 (23rd May 2017) - Boksebeld, M.; Kilin, V.; Géloën, A.; Ceccone, G.; Jaffal, A.; Schmidt, C.; Alekseev, S.; Lysenko, V.; Wolf, J. P.; Bonacina, L.; Souteyrand, E.; Chevolot, Y.; et al.
Abstract : SHG-active SiC nanoparticles were modified with folic acid for cancer-cell-specific labelling. Abstract : Interest in multiphoton microscopy for cell imaging has considerably increased over the last decade. Silicon carbide (SiC) nanoparticles exhibit strong second-harmonic generation (SHG) signal, and can thus be used as nonlinear optical probes for cell imaging. In this study, the surface of SiC nanoparticles was chemically modified to enable cancer-cell-specific labeling. In a first step, an aminosilane was grafted onto the surface of SiC nanoparticles. The resulting nanoparticles were further modified with folic acid, using an isothiocyanate-based coupling method. Nanoparticles from different functionalization steps were investigated by zeta potential measurement, colorimetric titration, infrared and ultraviolet-visible (UV-Vis) absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), and time-of-flight secondary ion mass spectrometry (ToF-SIMS). Characterization results confirmed successful covalent grafting of silane and folic acid to nanoparticle surface. Finally, the efficacy of these folate-modified SiC nanoparticles for cancer-cell-specific labeling was evaluated by multiphoton microscopy, by measuring SHG-emitting cell area on multiphoton images. The average cancer-cell labeling percentage was about 48%, significantly higher than for negative controls (healthy cells, competition assay and poly(ethylene glycol) modified-SiC nanoparticles), where it ranged between 10% and 15%. These results demonstrated good efficiency and specificity for these folate-modified SiC nanoparticles in cancer-cell-specific labeling.